How Does Social Currency Influence Prosocial Behavior? The Role of Collective Self-Esteem and Communication Network Heterogeneity - Gong, Xiaoxiao; Ye, Zuoliang; Liu, Binjie; Yu, Shengxian; Yan, Yufei (Frontiers in Psychology, 2021)
The social currency, one’s existing and potential resources in social networks and communities, has become more significant in the era of information technology. Meanwhile, the rapid development of Internet service, especially its application on mobile devices, brings many new contents of prosocial behaviors, which benefits both individuals and communities. Specifically, social currency plays a positive role in promoting prosocial behavior, forming positive personalities, promoting positive social adaptation, and contributing to human survival and social development. However, the theoretical research in this field still lags far behind the development of practice, and the research of the impact of social currency on prosocial behavior remains exceedingly scarce. Grounded in the social exchange theory, the present study collects totally 497 WeChat user questionnaires, constructs a model of the influence mechanism of social currency on prosocial behavior, and tests the hypothesis through hierarchical regression. According to the results obtained, social currency is positively associated with prosocial behavior, and users with a more social currency are more likely to act prosocially on their own. Individuals' prosocial behavior is then influenced by the social currency generated through collective self-esteem so that the perception of collective self-esteem can be considered as a mediating variable.. Moreover, the communication network heterogeneity moderates the above relationship, and the degree of heterogeneity will have different effects on the relationship of collective self-esteem. The obtained conclusions enrich the previous theoretical results of prosocial behavior and provided new insights for social managers to enhance the prosocial-related behaviors for the group, organization, and society.